2013
DOI: 10.3109/00207454.2013.850084
|View full text |Cite
|
Sign up to set email alerts
|

A national database of incidence and treatment outcomes of status epilepticus in Thailand

Abstract: Status epilepticus (SE) is a serious neurological condition. The national database of SE in Thailand and other developing countries is limited in terms of incidence and treatment outcomes. This study was conducted on the prevalence of status epilepticus (SE). The study group comprised of adult inpatients (over 18 years old) with SE throughout Thailand. SE patients were diagnosed and searched based on ICD 10 (G41) from the national database. The database used was from reimbursement documents submitted by the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 13 publications
4
45
0
Order By: Relevance
“…Status epilepticus affects 5-41/100,000 people annually and has a mortality rate up to 38% [1][2][3][4] and over 60% occurring after prolonged seizures duration [1]. Between 31-43% of cases will be refractory to first-line and second-line treatments [5,6], and this subset, termed refractory status epilepticus, has a mortality rate of 30% [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Status epilepticus affects 5-41/100,000 people annually and has a mortality rate up to 38% [1][2][3][4] and over 60% occurring after prolonged seizures duration [1]. Between 31-43% of cases will be refractory to first-line and second-line treatments [5,6], and this subset, termed refractory status epilepticus, has a mortality rate of 30% [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The overall mortality rate in the US is approximately 20% [4], in Thailand it is about 11.96% [5], and in Brazil it can reach up to 36.2% [11]. Hay et al [6] performed a retrospective study of patients admitted to an intensive care unit with the primary admission diagnosis of SE in ­Australia and New Zealand, and they found that mortality decreased greatly from 2.6% in 2000 to 0.75% in 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Only 45% of the patients in the study from central Thailand were 60-90 years of age [14]. We found the national mortality rate of SE to be 11.96% for all age groups [19], which was lower than in this elderly population (14.5%). Several factors were independently associated with poor outcomes at discharge (Table 3).…”
Section: Discussionmentioning
confidence: 81%
“…This study is a subgroup analysis of the previous study [31]. Another national study included all adult SE patients with all types of health insurance and treated in 2010 [19] which may be a part of this study. Some limitations exist, however.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation